Functional Consequences of Cocaine Expectation: Findings in a Nonhuman Primate Model of Cocaine Self-Administration - Porrino, Linda J. (Addict Biol, 2015)
Exposure to stimuli and environments associated with drug use is considered one of the most important contributors to relapse among substance abusers. Neuroimaging studies have identified neural circuits underlying these responses in cocaine-dependent subjects. But these studies are often difficult to interpret because of the heterogeneity of the participants, substances abused, and differences in drug histories and social variables. Therefore, the goal of this study was to assess the functional effects of exposure to cocaine-associated stimuli in a nonhuman primate model of cocaine self-administration, providing precise control over these variables, with the 2-[(14)C]deoxyglucose method. Rhesus monkeys self-administered 0.3 mg/kg/injection cocaine (n=4) under a fixed-interval 3-min (FI 3-min) schedule of reinforcement (30 injections/session) for 100 sessions. Control animals (n = 4) underwent identical schedules of food reinforcement. Sessions were then discontinued for 30 days, after which time monkeys were exposed to cocaine- or food-paired cues, and the 2DG experiment was conducted. The presentation of the cocaine-paired cues resulted in significant increases in functional activity within highly restricted circuits that included portions of the pre-commissural striatum, medial prefrontal cortex, rostral temporal cortex, and limbic thalamus when compared to control animals presented with the food-paired cues. The presentation of cocaine-associated cues increased brain functional activity in contrast to the decreases observed after cocaine consumption. Furthermore, the topography of brain circuits engaged by the expectation of cocaine is similar to the distribution of effects during the earliest phases of cocaine self-administration, prior to the onset of neuroadaptations that accompany chronic cocaine exposure.